International Corporate Strategic Alliances: Mergers & Acquisitions and Financial Value Creation - Ngwakwe, Collins C. (The Journal of Accounting and Management, 2024)
Mergers and acquisitions are important financial and economic strategic alliance tools of the modern corporation. Objective: this paper aims to analyse the value creation implication from global strategic mergers and acquisitions. Prior work: the paper inclines on the synergy theory of mergers and acquisitions. Method: reliant on the synergy theory, the paper is quantitative to examine the effectiveness of the number of global alliances on the financial value from mergers and acquisitions. Data were collected from the Institute for Mergers, Acquisitions and Alliances for thirty-nine years (1985 - 2023). The data were analysed with the aid of OLS regression statistics. Results: tested at an alpha value of 0.05, the results show positive and significant effect at a p-value of P<0.0001, which confirms that global mergers and acquisitions produce a highly significant and positive financial value even after a long-term period of thirty-nine years. Implication: the paper has implication for business executives on the value of international alliance; and for business schools as a case that bolsters the synergy theory of merger and paves a new agenda for future research. Value: the paper applies a unique model by using global data on strategic alliances for an extended period of over three decades and debunks uncertainties in research to show that mergers and acquisitions can produce significant financial value into the future when done rightly, which is across international boundaries.